2016
DOI: 10.1002/jcu.22366
|View full text |Cite
|
Sign up to set email alerts
|

The detection of viable myocardium by low‐dose dobutamine stress speckle tracking echocardiography in patients with old myocardial infarction

Abstract: Global strain at LDDSE is superior to semi-quantitative wall-motion analysis with LDDSE for the assessment of VM. When the multivariable analysis and the parallel tests are combined, LS combined with LSr can be considered an independent predictor of VM. LVEF is improved after PCI in patients with VM and OMI. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44:545-554, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Seventythree percent have their total cholesterol >250 mg /dl, and 60% was a smoker. These findings were expected in those ischemic heart disease patients as the mentioned risk factor is common in these selected patients (Li et al, 2016). Revascularization has become an important therapeutic strategy for patients with old MI.…”
Section: Discussionsupporting
confidence: 53%
“…Seventythree percent have their total cholesterol >250 mg /dl, and 60% was a smoker. These findings were expected in those ischemic heart disease patients as the mentioned risk factor is common in these selected patients (Li et al, 2016). Revascularization has become an important therapeutic strategy for patients with old MI.…”
Section: Discussionsupporting
confidence: 53%
“…[29,30] 2D-STE is used to evaluate VM by measuring the LV global and regional strain and strain rate recently. [31,32] Some studies have shown that 2D-STE has high sensitivity and appropriate specificity for early identification of VM in patients with AMI by strain and strain rate measurements. [33]…”
Section: Discussionmentioning
confidence: 99%
“…The combination of low‐dose dobutamine stress echo (LDDSE) and STI has been used for detection of viable myocardium in patients with old myocardial infarction. In a recent study LS at LDDSE was superior to semiquantitative wall‐motion analysis with LDDSE for the assessment of viable myocardium. In the multivariable analysis LS combined with LSR was considered as an independent predictor of viable myocardium and LVEF was improved after PCI in these patients.…”
Section: Deformation Imaging In Ischemic Cardiomyopathymentioning
confidence: 97%